Financial Innovation Cost Awareness of Technology Financial Inclusion - Eid, Ali Ibrahim Abu; Nussir, Nour Ali; Jahmani, Ashraf; Baqader, Saleh Mohammed; Alataibi, Mahmud; Hariri, Mohammad; Alabdullatif, Sultan Abdullah; Bazhair, Ayman Hassan (Journal of Posthumanism, 2025)
Investigating financial innovation, driven by digital technologies that are transforming industries, the move by firms in the financial sector is to include financial inclusion and consumer expenditure. Evidence from the literature on financial innovation and the relation between high-cost sensitivity has been examined by consumers and is broadened through an exploratory study of secondary data. This study examines the impact of mobile banking, peer-to-peer lending platforms, and mobile wallet applications from fintech on human consumer finance conduct in financial choices. Products of fintech creation provide, according to this study, customers appreciating financial cost empowerment alongside a responsibility to deliver higher levels of financial literacy to respond to a much more nuanced and broader choice collection. This inquiry additionally explores the obstacles and opportunities of employing technology to improve financial inclusion for the underprivileged and excluded. It categorises access struggles and ruling setbacks. Moreover, this examination acknowledges innovation’s power to supply custom-made financial facilities that would close the disparities between established money management practices and the requirements of poverty-stricken areas. The principal inferences indicate that financial inventions have indeed raised client expense liking and enforced changes in financial institutions; then again, they have also showcased integration in financial decision-making. The paper has primed to pull out the significance of widespread financial education and improve electronic access to make sure that the revolution of fintech will be a general ambitious progression of a more just financial ecosystem. The decision and recommendations of this paper qualm targeted policy interventions and mutual effort to nurture an ambience of inclusiveness that will allow the novelty innovation of financial and benefit for digital finance leave of nobody.